2013
DOI: 10.1016/j.ymgme.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement therapy with galsulfase in 34 children younger than five years of age with MPS VI

Abstract: The prescribed dosage of 1mg/kg IV weekly with galsulfase ERT is shown to be safe and effective in slowing and/or improving certain aspects of the disease, although patients should be closely monitored for complications associated with the natural history of the disease, especially cardiac valve involvement and spinal cord compression. A long-term follow-up investigation of this group of children will provide further information on the benefits of early treatment as well as disease progression and treatment ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 17 publications
1
47
0
1
Order By: Relevance
“…However, the initiation of therapy before this age may have additional benefits and/or prevent some complications (McGill et al, 2010;Furujo et al, 2011;Horovitz et al, 2013). This study presents follow-up data for two Brazilian siblings diagnosed with MPS VI, enabling a comparison of clinical and laboratory outcomes of the effects of ERT initiated at different ages.…”
Section: Discussionmentioning
confidence: 99%
“…However, the initiation of therapy before this age may have additional benefits and/or prevent some complications (McGill et al, 2010;Furujo et al, 2011;Horovitz et al, 2013). This study presents follow-up data for two Brazilian siblings diagnosed with MPS VI, enabling a comparison of clinical and laboratory outcomes of the effects of ERT initiated at different ages.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestations of heart disease in patients with MPS VI are of great relevance due to the increased morbidity and mortality, associated with poorer quality and lower life expectancy [1][2][3][4][5][6][7][8][9]. The heart valves are the structures most affected by the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Its treatment options include hematopoietic cell transplantation and ERT, which is the most commonly used. The benefit of ERT in cardiovascular complications is in delaying the natural progression of valvular disease, especially if started early (before 5 years of age) and in the absence of pre-established cardiac complications [7][8][9]. However, in order to achieve this benefit, it is of the utmost importance that the treatment be done continuously, without interruption [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infusion-related reactions were described in several studies and case reports, but probable IgE-mediated allergy has been reported only in one patient. Frequently observed reactions were mild to moderate infusion-related reactions, which were easily resolved by slowing or temporary interruption of the infusion and/or administration of additional antihistamines, antipyretics, and corticosteroids (Harmatz et al 2006;Horovitz et al 2013). Here we report two children with MPS VI who experienced IgE-mediated hypersensitivity reactions with galsulfase and could receive ERT after successful rapid desensitization.…”
Section: Introductionmentioning
confidence: 99%